2024
DOI: 10.1186/s12943-023-01904-w
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic challenges in peripheral T-cell lymphoma

Yunpeng Luan,
Xiang Li,
Yunqi Luan
et al.

Abstract: Peripheral T-cell lymphoma (PTCL) is a rare and heterogeneous group of hematological malignancies. Compared to our knowledge of B-cell tumors, our understanding of T-cell leukemia and lymphoma remains less advanced, and a significant number of patients are diagnosed with advanced stages of the disease. Unfortunately, the development of drug resistance in tumors leads to relapsed or refractory peripheral T-Cell Lymphomas (r/r PTCL), resulting in highly unsatisfactory treatment outcomes for these patients. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 149 publications
0
2
0
Order By: Relevance
“…Despite significant advancements in treatments in recent years, the pathogenesis mechanisms of lymphoma remain incompletely elucidated. Currently, the lack of effective treatment options for refractory or drug-resistant lymphomas remains a persistent challenge ( Brice et al., 2021 ; Bishop et al., 2022 ; Sehgal et al., 2022 ; Luan et al., 2024 ). Therefore, it is imperative to unravel the key mechanisms that govern tumor behavior and to develop clinically relevant biomarkers and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advancements in treatments in recent years, the pathogenesis mechanisms of lymphoma remain incompletely elucidated. Currently, the lack of effective treatment options for refractory or drug-resistant lymphomas remains a persistent challenge ( Brice et al., 2021 ; Bishop et al., 2022 ; Sehgal et al., 2022 ; Luan et al., 2024 ). Therefore, it is imperative to unravel the key mechanisms that govern tumor behavior and to develop clinically relevant biomarkers and therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, NF-κB is involved in proliferative signaling in various lymphoid malignancies, and although further investigation is needed, gene expression profiling studies have shown increased expression of NF-κB-related genes in PTCL, and the induction of apoptosis in PTCL cells by NF-κB inhibitors supports the notion that this pathway plays a significant role in PTCL. Moreover, accumulating evidence suggests the involvement of viral components in multidrug chemotherapy resistance in lymphoma cells, with some mechanisms potentially mediated through cancer-causing viruses altering disease signaling pathways [ 11 ].…”
Section: Introductionmentioning
confidence: 99%